Perspectives on Spain’s legislative experience providing access to healthcare to irregular migrants: a qualitative interview study - Renee Y Hsia; Diana Gil-González (BMJ Open)
Objectives In 2018, Spain adopted a national law that significantly expanded healthcare access to all residents, including undocumented migrants. This was a substantial shift from a more restrictive system of coverage in previous years. However, irregular migrants continue to experience challenges accessing healthcare in Spain. This study aimed to describe the legislative and administrative barriers to implementation of this law from the perspective of providers and administrators of the healthcare system.Design We interviewed 12 individuals using a semistructured format.Setting Spain.Participants 12 participants were interviewed; 7 males, 5 females. Participants included Spanish healthcare workers, government officials, hospital administrators, individuals working with non-governmental organisations focused on the provision of healthcare, and experts studying healthcare for underserved populations.Primary and secondary outcome measures Interviews delved into personal experiences and knowledge of the entitlements and barriers of providing or trying to access care for undocumented migrants.Results The interviews yielded eight key themes: (1) context of universal healthcare in Spain pre-2012; (2) erosion of trust as rationale for more restrictive policies of 2012; (3) challenges of the 3-month residency requirement; (4) areas of ambiguity: exceptions in the 2012 Royal Decree Law not discussed in the 2018 Royal Decree Law; (5) jurisdictional authority and conflicts between national and AC government; (6) near impossibility of obtaining documentation for exportation of healthcare; (7) difficulties obtaining necessary paperwork to register residency; and (8) rise of NGOs to provide support to irregular migrants.Conclusion While there has been a general political movement to expand healthcare access for undocumented migrants in Spain, there remains a fundamental need to clarify the legal entitlements for undocumented migrants nationally and create administrative consistency across autonomous communities for providing health cards for undocumented migrants. Other countries may be able to draw lessons from the Spanish experience about the legislative frameworks surrounding access to healthcare for undocumented migrants.